Breast Milk Iodine Concentration Is a More Accurate Biomarker of Iodine Status Than Urinary Iodine Concentration in Exclusively Breastfeeding Women. Issue 4 (22nd February 2017) - Dold, Susanne; Zimmermann, Michael B; Aboussad, Abdelmounaim; Cherkaoui, Mohamed; Jia, Qingzhen; Jukic, Tomislav; Kusic, Zvonko; Quirino, Antonio; Sang, Zhongna; San Luis, Teofilo OL; Vandea, Elena; Andersson, Maria
Abstract: Background: Iodine status in populations is usually assessed by the median urinary iodine concentration (UIC). However, iodine is also excreted in breast milk during lactation; thus, breast milk iodine concentration (BMIC) may be a promising biomarker of iodine nutrition in lactating women. Whether the mammary gland can vary fractional uptake of circulating iodine in response to changes in dietary intake is unclear. Objective: We evaluated UIC and BMIC as biomarkers for iodine status in lactating women with a wide range of iodine intakes. Methods: We recruited 866 pairs of lactating mothers and exclusively breastfed infants from 3 iodine-sufficient study sites: Linfen, China ( n = 386); Tuguegarao, Philippines ( n = 371); and Zagreb, Croatia ( n = 109). We also recruited iodine-deficient lactating women from Amizmiz, Morocco ( n = 117). We collected urine and breast milk samples and measured UIC and BMIC. Results: In the 3 iodine-sufficient sites, a pooled regression analysis of the estimated iodine excretion revealed higher fractional iodine excretion in breast milk than in urine at borderline low iodine intakes. In contrast, in the iodine-deficient site in Morocco, a constant proportion (∼33%) of total iodine was excreted into breast milk. Conclusions: In iodine-sufficient populations, when iodine intake in lactating women is low, there is increased partitioning of iodine into breast milk. For this reason, maternal UIC alone may not reflect iodine status, and BMIC should also be measured to assess iodine status in lactating women. Our data suggest a BMIC reference range (2.5th and 97.5th percentiles) of 60–465 μg/kg in exclusively breastfeeding women. This trial was registered at clinicaltrials.gov as NCT02196337.